Proximity-induced superconductivity in monolayer 1T’-WTe2 - Tong, Zheng Jue (Nanyang Technological University, 2020)
The Transition Metal Dichalcogenide (TMD), 1T'-WTe2 has gained a lot attention, recently, owing to predictions of the Quantum Spin Hall effect, a 2D topological state that has potential application in Quantum Information technologies when combined with superconductivity. We report molecular beam epitaxy of van-der-Waals heterostructures of 1T'-WTe2 and the layered type-II superconductor NbSe2. Induced superconductivity in WTe2 is confirmed by scanning tunneling spectroscopy (STS) down to 500mK. We analyze the measured superconducting gap within the framework of the McMillan equations, describing both substrate and WTe2 epilayer within a consistent framework of multi-band superconductivity.